Treatment of Pisotriquetral Arthritis by Pyrocarbon Interposition Arthroplasty - Bellemère, Philippe; Aribert, Marion; Choughri, Hussein; Leroy, Marc; Gaisne, Etienne (Journal of Wrist Surgery, 2018)
Purpose Pisiformectomy is the baseline treatment for pisotriquetral arthritis when medical treatment fails to address the problem. This operation may lead to loss of mobility and strength in the wrist. This study reports the short-term outcomes of a new technique for treating pisotriquetral arthritis using a pisotriquetral interposition arthroplasty with a pyrocarbon implant.Patients and Methods We performed a clinical and radiographic study on a series of eight patients who received this treatment at a mean follow-up of 2.8 years. We also studied the mobility of the implant and did assessed articular instability using dynamic radiology and fluoroscopy.Results We observed one proximal dislocation of the implant in one hand which was reoperated to reposition the implant and strengthen the capsule. All patients were satisfied or very satisfied with their operation and had an average functional recovery period of 1.6 months. At the last follow-up, the Mayo Wrist Score (MWS), Quick Disability of Arm Shoulder and Hand (QDASH), and Patient-Rated Wrist Evaluation (PRWE) scores were 89, 18, and 20, respectively. Postoperatively, there was a 22% improvement in the grip strength of the wrists as well as improved mobility, mainly as regards the radioulnar deviation (47% improvement) and the Visual Analogue Scale (VAS) pain scores decreased from 8 preoperatively to 2 at the latest follow-up. The functional radiologic and fluoroscopic study reported good adaptive mobility of the implant in all the patients, without any indication of pisotriquetral joint instability.Conclusion The short-term results of pisotriquetral arthroplasty using the Pyrocardan implant are encouraging. This new surgical solution appears to be a valid alternative to pisiformectomy or pisotriquetral arthrodesis. Long-term studies are required to confirm these preliminary findings.
Keywords: arthroplasty; wrist; pisotriquetral joint; pyrocarbon; pyrocardan